2020
DOI: 10.1080/10942912.2020.1781167
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and rheological properties of fruit and vegetable juices as affected by high pressure homogenization: A review

Abstract: In recent years, the consumers' demands for fruit and vegetable juices (F&VJ), such as higher nutritive values, minimal processing and high quality have been growing rapidly. High pressure homogenization (HPH) is a non-thermal technology that has been widely studied as a partial or total substitute for thermal fluid food processing. The present work summarized the effect of HPH on the particle size distribution (PSD), microstructure, pulp sedimentation (PS), serum cloudiness (SC) or turbidity, color change (CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 79 publications
(123 reference statements)
1
26
0
Order By: Relevance
“…Due to the significant changes in the viscosity of juices observed during storage and the differences detected in the discrimination tests (Tables 2, 3), the rheological properties of the six juices included in the descriptive sensory profile were studied. Rheological properties of juices are affected by various quality factors, such as the composition and contents of monomeric and polymeric carbohydrates in the fruit [36,37]. Depectination and clarification of blackcurrant juice (or juice from other similar berries) using enzymes result in more Newtonian fluid behaviour in comparison to the non-Newtonian behaviour of the initial berry puree [37,38].…”
Section: Changes In Rheological Properties During Storagementioning
confidence: 99%
“…Due to the significant changes in the viscosity of juices observed during storage and the differences detected in the discrimination tests (Tables 2, 3), the rheological properties of the six juices included in the descriptive sensory profile were studied. Rheological properties of juices are affected by various quality factors, such as the composition and contents of monomeric and polymeric carbohydrates in the fruit [36,37]. Depectination and clarification of blackcurrant juice (or juice from other similar berries) using enzymes result in more Newtonian fluid behaviour in comparison to the non-Newtonian behaviour of the initial berry puree [37,38].…”
Section: Changes In Rheological Properties During Storagementioning
confidence: 99%
“…The food industry has shown an increased interest in the producing of healthier, high quality, minimally processed, and more natural VJs and concentrates. Nonthermal processing of VJs such as high‐pressure processing, ultrasonication, pulsed electric field, irradiation, and pulsed light offers an alternative to conventional thermal processing to meet consumer demands for convenient, high quality, and minimally processed food products (Salehi, 2020c, 2020d, 2020e). Some researchers suggested that these methods is an interesting alternative to improve the physical and nutritional properties of VJs.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers suggested that these methods is an interesting alternative to improve the physical and nutritional properties of VJs. Also, these treatments destroy harmful microorganisms at low or moderate temperatures without significantly changing the organoleptic and nutritional properties of VJs (Salehi, 2020c, 2020d, 2020e).…”
Section: Introductionmentioning
confidence: 99%
“…[12] Apple pomace 0.335-764 W/cm 2 5-55 min 16-40 -Extracts obtained by US showed higher antioxidant activity [13] Avocado puree 20 kHz; 375 W/cm 2 0-10 min -50% US significantly changes particle size, color, AV and polyphenol oxidase activity of avocado puree dilutions. [14] Bayberry juice 20 kHz; 90, 181, 271, 362 and 452 W/cm 2 1-12 min -20, 40, 60, 80 and 100% The inactivation rates of peroxidase by US treatment were also higher than those by US with cooling at the same US intensity and time. Kinetic parameters for peroxidase by US and US with cooling treatment were lower than those of polyphenol oxidase, inferring its more US resistant.…”
mentioning
confidence: 91%
“…The food industry has shown an increased interest in the producing of healthier, high quality, minimally processed and more natural food products. [1,2] The quality of FVJ is defined by their physical properties and enzymatic, microbiological, and sensory characteristics and stability . [3,4] In addition, US can be used as a processing aid in phenolic compound extraction, crystallization, freezing, emulsification, filtration and drying.…”
Section: Introductionmentioning
confidence: 99%